1986
DOI: 10.1128/jcm.24.1.145-.1986
|View full text |Cite
|
Sign up to set email alerts
|

Increased detection of prolylaminopeptidase in Neisseria meningitidis by Identicult-Neisseria

Abstract: a rapid enzymatic method with chromogenic substrates, was tested in our laboratories for the identification of Neisseria gonorrhoeae, Neisseria meningitidis, and Neisseria lactamica. The test correlated very highly in its identification of pathogenic Neisseria spp. with modified New York City fermentation medium. Identicult-Neisseria appeared to be more sensitive in its detection of prolylaminopeptidase activity in N. meningitidis than most of the currently available systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
2
1
Order By: Relevance
“…We found that 26.3'X of the N . meningitidis strains were positive for both GAP and PAP; this is considerably lower than the 92.5% reported by Sperry et al (1986) who advocated that N . meningitidis strains be regarded as PAP-positive.…”
Section: Discussioncontrasting
confidence: 60%
“…We found that 26.3'X of the N . meningitidis strains were positive for both GAP and PAP; this is considerably lower than the 92.5% reported by Sperry et al (1986) who advocated that N . meningitidis strains be regarded as PAP-positive.…”
Section: Discussioncontrasting
confidence: 60%
“…Methods for the identification of Neisseria spp. include carbohydrate degradation tests (8,13), chromogenic enzyme substrate tests (6,7,16,17), and combinations of these two approaches (14,15). Conventional procedures use cystinetryptic digest agar (CTA) base medium with added carbohydrates and may require prolonged incubation for some isolates before results are available (13).…”
mentioning
confidence: 99%
“…Most recently, identification methods with specific chromogenic enzyme substrates have become available for rapid identification of Neisseria spp. that grow on selective medium (i.e., N. gonorrhoeae, N. meningitidis, and N. lactamica) (6,7,14,16,17). These systems also provide a presumptive identification of Branhamella catarrhalis, an organism of recognized clinical importance that can also be occasionally recovered on selective medium (e.g., modified Thayer-Martin [MTMI and Martin-Lewis agars) (4; G. V. Doern, Clin.…”
mentioning
confidence: 99%